Literary Study of the Influence of Monopoly Game Media in Increasing PKN Learning Results in Elementary Schools: Studi Literartur Pengaruh Media Permainan Monopoli Dalam Meningkatan Hail Belajar PKN di Sekolah Dasar - Ayu Surya Adhaeni Surya; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2022)
This research is a literature study that analyzes the results of various types of previous studies that have relevant titles. This type of research is a literature review and analyzes research that uses quantitative research and classroom action research. This study aims to analyze the use of monopoly game media in improving Civics learning outcomes in elementary schools. The data collection technique in this literature study research uses the documentation method. The source of data in this study is secondary data obtained from the results of research that has been carried out by previous researchers. This shows that the use of monopoly game media helps students in improving student learning outcomes in Civics material. In addition, monopoly game media can help student learning and make it easier for educators to deliver subject matter.